DEF inhibition filler, anti-crack UHPC, and preparation method and application of anti-crack UHPC
By using DEF inhibitory filler in UHPC, combined with porous calcined straw particles, phase change materials and nano-SiO2 modified plant fibers, the problem of UHPC cracking in high ground and high ground stress environment is solved, and the structural stability and durability are improved.
Patent Information
- Application Number
- CN202510630153.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-16
AI Technical Summary
Ultra-high performance concrete (UHPC) is prone to cracking problems in high ground stress and high ground temperature environments such as deep buried tunnels, which affects the safety and durability of the structure.
Using DEF inhibitory filler, combining porous calcined straw particles with phase change material (PCM), using technologies such as SiO2/PVA encapsulation layer and nano SiO2 modified plant fibers, a multi-mechanical synergistic cracking system is built to reduce hydration heat and self-shrinkage stress, and inhibit the occurrence of delayed ettringite reaction (DEF) and temperature stress cracks.
It effectively suppresses the occurrence of DEF phenomenon and temperature stress cracks, improves the service stability and durability of UHPC in high ground and high ground stress environments, and ensures structural integrity and safety.
Smart Images

Figure CN120172670A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and particularly relates to a DEF inhibitor filler, crack-resistant UHPC, and a preparation method and application thereof. Background Art
[0002] Disclosing the information of this background art section is only intended to enhance the overall understanding of the present invention, and is not necessarily regarded as an admission or any form of implication that this information constitutes prior art already known to those of ordinary skill in the art.
[0003] Tunnel and underground engineering construction will face different technical problems due to different geological environments. Especially in deep-buried tunnels under high ground stress and high ground temperature environments, their safety and durability both face severe challenges. In deep-buried underground projects, the extreme environmental conditions such as high ground stress, high ground temperature, and low humidity that concrete structures are in for a long time pose strict requirements on the crack resistance and long-term durability of materials.
[0004] Ultra-High Performance Concrete (UHPC) has been widely used in deep-buried engineering fields such as tunnels, underground spaces, and deep mines due to its excellent mechanical properties, durability, and low permeability. However, UHPC faces serious cracking problems in practical applications, which can lead to a decline in structural integrity, impaired durability, and even affect overall safety. The cracking problems of UHPC stem from the coupled action of multiple factors. Especially in deep-buried environments, these cracking mechanisms are further amplified, mainly including: (1) Autogenous shrinkage cracks: UHPC uses an ultra-low water-binder ratio, resulting in a lack of free water inside during the later stage of hydration reaction. The water in capillary pores changes from saturated to unsaturated, forming capillary negative pressure, which triggers significant autogenous shrinkage. The low humidity conditions in deep-buried environments further exacerbate water loss, making autogenous shrinkage cracks more likely to occur and affecting the structural integrity; (2) Hydration heat cracks: A large amount of reactive admixtures (such as silica fume, slag micro-powder, etc.) are incorporated into UHPC, increasing the hydration rate of cement. In deep-buried high geothermal environments, the heat released during hydration is difficult to dissipate, and the internal temperature rises rapidly, resulting in volume expansion. During the subsequent cooling process, shrinkage occurs again, thus generating temperature stress cracks; (3) Delayed ettringite formation (DEF) cracks: In deep-buried environments, concrete is exposed to relatively high temperatures (such as exceeding 70 °C) for a long time, which can induce the secondary hydration reaction of aluminate phases in cement, generating expansive ettringite (AFt), causing volume expansion and cracking; (4) Long-term thermal stress cracks, mainly triggered by long-term temperature gradients and low-frequency thermal fluctuations: During the construction stage, the heat released by cement hydration causes the temperature of UHPC to be much higher than that of the surrounding rock. During the service stage, the heat of the surrounding rock continuously acts on the concrete surface layer. However, due to the thermal inertia or local thermal disturbances (such as underground water flow, start-stop of ventilation systems) inside the UHPC engineering structure, the temperature distribution is uneven. This spatial temperature gradient leads to differences in expansion amounts in different regions, triggering alternating expansion and contraction. Long-term repeated action will cause micro-cracks to gradually expand in stress concentration areas through the low-cycle fatigue effect, eventually forming macroscopic cracks, resulting in significant structural cracking and reducing the durability of the project. Summary of the Invention
[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a DEF-inhibiting filler, crack-resistant UHPC, its preparation method and application. The PCM and porous carrier encapsulation technology is used to inhibit the DEF phenomenon, combined with the whole-process shrinkage compensation of magnesia calcined at different particle sizes and different temperatures and shrinkage reducing agents. The internal curing is realized by modifying plant fibers with nano-SiO2, and nano-SiO2 aerogel is incorporated to reduce the thermal conductivity, constructing a multi-mechanism synergistic crack-resistant system to achieve the whole-process crack control of ultra-high performance concrete in high ground stress and high geothermal environments and improve the long-term service stability.
[0006] In order to achieve the above purpose, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a DEF-inhibiting filler, comprising porous calcined straw particles, and a phase change material adsorbed inside the calcined straw particles; the phase change material is dispersed with nano-aluminum oxide; the outside of the calcined straw particles is coated with a SiO2 / PVA encapsulation layer, and a silane coupling agent modification layer and a shrinkage reducing agent modification layer are sequentially arranged on the surface of the SiO2 / PVA encapsulation layer.
[0007] Optionally, the raw materials for preparing the DEF-inhibiting filler include the following components in parts by weight: 80-100 parts of calcined straw particles, 20-30 parts of phase change material, 2-3 parts of nano-aluminum oxide, 2-3 parts of silica sol, 0.2-0.3 parts of polyvinyl alcohol, 0.5-0.7 parts of silane coupling agent, and 5-7 parts of shrinkage reducing agent.
[0008] In a second aspect, a method for preparing the above DEF-inhibiting filler includes: S1. Add nano-aluminum oxide to the molten phase change material, stir evenly and then mix with the calcined straw particles to adsorb the phase change material into the voids of the calcined straw particles, and cool down to below the phase change temperature of the phase change material to obtain a filler adsorbed with the phase change material; S2. Dissolve silica sol and polyvinyl alcohol in deionized water to obtain an encapsulation liquid, immerse the filler adsorbed with the phase change material in the encapsulation liquid, take it out and then modify it with a silane coupling agent and a shrinkage reducing agent in sequence to obtain the DEF-inhibiting filler.
[0009] In a third aspect, a crack-resistant UHPC includes the following components in parts by weight: 360-520 parts of high sulfate-resistant cement, 36-52 parts of silica fume, 36-52 parts of calcined straw ash, 7-36 parts of nano-silica modified plant fiber, 800-1000 parts of fine aggregate, 800-1000 parts of coarse aggregate, 39-78 parts of steel fiber, 10-15 parts of low-temperature calcined nano-magnesium oxide, 8-12 parts of high-temperature calcined micron-sized magnesium oxide, 80-200 parts of the above DEF-inhibiting filler, 5-18 parts of nano-silica aerogel, 120-130 parts of water, 2-6 parts of shrinkage reducing agent, and 5-10 parts of water reducing agent.
[0010] In a fourth aspect, a method for preparing the above crack-resistant UHPC includes the steps: S3. Mix and dry-mix high sulfate-resistant cement, silica fume, calcined straw ash, fine aggregate, coarse aggregate, nano-magnesium oxide, micron-sized magnesium oxide, shrinkage reducing agent, fine aggregate, DEF-inhibiting filler, and shrinkage reducing agent to obtain a dry-mixed material; S4. Add 70% of the total amount of water to the dry-mixed material, stir, then add a high-range water reducing agent, stir, then add the remaining 30% of the total amount of water and nano-silica aerogel, stir, and then add nano-silica modified plant fiber and steel fiber to obtain a mixed slurry; S5. Cast the mixed slurry into a mold and cure it at a temperature consistent with the high geothermal environment to obtain crack-resistant UHPC.
[0011] In a fifth aspect, the application of the above-mentioned crack-resistant UHPC includes applications in geothermal projects, deep-buried tunnels, nuclear power plants or infrastructure construction in high geothermal environments.
[0012] The beneficial effects of the present invention are as follows: 1. The present invention uses DEF inhibitor fillers to inhibit the delayed expansion reaction (DEF) in high geothermal environments and optimize the service stability of concrete. The DEF inhibitor filler consists of calcined straw ash particles, a phase change material (PCM), and an SiO2 / PVA encapsulation layer. The phase change energy storage and temperature regulation mechanism effectively reduces the peak value of hydration heat through the endothermic phase change process of the PCM at 40 - 60°C, avoiding high-temperature-induced sulfate attack and DEF expansion damage caused by internal hydration reactions. The surface is encapsulated with silica sol - polyvinyl alcohol to improve the encapsulation stability of the PCM, prevent material decomposition or leakage in high-temperature environments, and enhance the interfacial bonding force between the aggregate and the cement matrix. Further, a shrinkage reducing agent (SRA) is sprayed on the surface to effectively reduce the migration of internal moisture in the concrete into the DEF inhibitor filler, reduce autogenous shrinkage stress, and ensure long-term durability. The multi-level pore structure formed after calcining the straw ash at 500 - 600°C has a water storage function, which can absorb the excess moisture in the cement paste in the initial stage and slowly release the moisture through the humidity gradient in the later stage to compensate for autogenous drying shrinkage; the endothermic phase change of the DEF inhibitor filler reduces temperature fluctuations, while the moisture released from the porous structure reduces drying shrinkage. The two jointly inhibit the propagation of microcracks through the water storage and temperature control mechanisms, achieve the effect of internal curing, and further reduce the occurrence of shrinkage cracks.
[0013] 2. In the ultra-high performance concrete (UHPC) of the present invention, calcined straw ash and micron / nano magnesium oxide are respectively incorporated, which can effectively reduce the hydration heat and inhibit the autogenous shrinkage of the concrete: Barley straw ash at different calcination temperatures is used as a partial substitute for cement, which can reduce the release of hydration heat, lower the internal temperature rise of the concrete, and prevent cracks caused by thermal stress. Other materials such as sulfoaluminate-based expansive agents will exacerbate the delayed ettringite reaction in high geothermal environments, or calcium oxide-based expansive agents will expand too fast in the early stage in high geothermal environments and cannot compensate for the late-stage cold shrinkage, increasing the risk of net shrinkage; neither can work stably in high geothermal environments. The hydration product Mg(OH)2 of magnesium oxide does not decompose at high temperatures, and the synergistic effect of micron-sized and nano-sized magnesium oxide realizes the full-process expansion compensation under high geothermal conditions through the differences in particle size and calcination temperature. The added plant fibers have the effect of internal curing, which can achieve multi-scale crack control and improve the crack resistance of UHPC: By modifying plant fibers with nano-SiO2 of different lengths, a reinforced network for bridging cracks is constructed inside the concrete: Short fibers (3 - 6 mm) can bridge micro-cracks and improve the early crack resistance; long fibers (6 - 12 mm) can effectively hinder the expansion of large cracks and improve the tensile toughness; The modification of nano-SiO2 can enhance the interfacial bonding force between the fiber and the cement matrix, improve the mechanical properties, and enhance the water absorption / water release capacity of the fiber, optimizing the internal curing effect. Nano-silica aerogel can optimize the temperature gradient of the concrete and improve the long-term durability: The low thermal conductivity of nano-silica aerogel can significantly reduce the overall thermal conductivity of the concrete, enabling it to reduce the heat transfer from the surrounding rock in the deep-buried high geothermal environment and avoid temperature stress concentration; Its low thermal conductivity can also improve the thermal expansion characteristics of the concrete, reduce cracks caused by temperature stress, and improve the long-term service performance of the concrete in high geothermal environments; By optimizing the aerogel dosage, on the premise of ensuring the mechanical properties, the service stability of UHPC can be further improved, enabling it to adapt to long-term engineering applications in extreme environments. Description of the Drawings
[0014] The specification drawings forming a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention.
[0015] Figure 1 It is a schematic technical route diagram of the DEF inhibitor filler and crack-resistant UHPC in the examples. Detailed Embodiments
[0016] It should be noted that the following detailed descriptions are all exemplary and are intended to provide a further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs.
[0017] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular forms are also intended to include the plural forms. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they specify the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0018] A typical embodiment of the present invention provides a DEF-inhibiting filler, which includes porous calcined straw particles, and a phase change material is adsorbed inside the calcined straw particles; nano-aluminum oxide is diffusely distributed in the phase change material; the outside of the calcined straw particles is coated with a SiO2 / PVA encapsulation layer, and a silane coupling agent modification layer and a shrinkage reducing agent modification layer are sequentially arranged on the surface of the SiO2 / PVA encapsulation layer.
[0019] Optionally, the DEF-inhibiting filler includes the following raw materials in parts by weight for preparation: 80-100 parts of calcined straw particles, 20-30 parts of phase change material, 2-3 parts of nano-aluminum oxide, 2-3 parts of silica sol, 0.2-0.3 parts of polyvinyl alcohol, 0.5-0.7 parts of silane coupling agent, and 5-7 parts of shrinkage reducing agent.
[0020] The calcined straw particles provide the basic shape for the DEF-inhibiting filler.
[0021] The phase change material endows it with the ability of phase change temperature control; a SiO2 / PVA encapsulation layer is arranged on the outside for encapsulating the internal phase change material, which has a certain strength and can prevent the shell structure of the DEF-inhibiting filler from being damaged during the mixing process with concrete.
[0022] The silane coupling agent modification layer serves as an intermediate layer between the encapsulation layer and the shrinkage reducing agent modification layer, and its functions include: closing the surface micropores to prevent the leakage of the phase change material and the intrusion of moisture; strengthening the interfacial bonding between the SiO2 / PVA encapsulation layer and the shrinkage reducing agent modification layer to ensure the integrity of the multi-layer structure; indirectly supporting the function of the shrinkage reducing agent, and enabling the shrinkage reducing agent to effectively regulate the interfacial behavior of concrete by stabilizing the filler structure.
[0023] The functions of the shrinkage reducing agent modification layer include: inhibiting the shrinkage cracking of concrete and enhancing the durability of the filler-concrete interface; regulating the moisture migration behavior to prevent the intrusion of moisture and the leakage of the phase change material (PCM) in a high geothermal environment; enhancing the interfacial chemical bonding to ensure the coordinated stress of the DEF-inhibiting filler and concrete.
[0024] Optionally, 25-35 parts of deionized water are also added during the preparation process of the DEF-inhibiting filler, and the deionized water is used to prepare the SiO2 / PVA encapsulation layer.
[0025] Optionally, the calcined straw particles have a particle size of 1 - 3 mm and a porosity of 60 - 70%, which provides a certain strength for the DEF inhibitor filler. The surface layer of the prepared DEF inhibitor filler is relatively thin, and the particle size is also about 1 - 3 mm. The small particle size filler shortens the heat transfer path, can improve the overall thermal conductivity of the concrete, accelerate the response speed of the phase change material (PCM), and is more suitable for the thermal management requirements of high geothermal environments. The micropores on the surface of the small particle size filler are more easily and evenly covered by encapsulating materials such as silica sol / PVA, reducing the risk of PCM leakage. The small particle size makes the filler tend to be stressed synergistically as a whole, which can make up for the strength disadvantage of the biomass filler.
[0026] Optionally, the raw material of the calcined straw particles is highland barley straw, which comes from agricultural waste along the project line.
[0027] Optionally, the phase change material includes one or more of palmitic acid, stearic acid, lauric acid, and myristic acid; by controlling the proportion of different components, the phase change temperature of the phase change material is 50 - 60°C; the melting point of stearic acid (C 18 H 36 O2) is about 69°C, the melting point of lauric acid (C 12 H 24 O2) is about 44°C, the melting point of myristic acid (C 14 H 28 O2) is about 54°C. Fatty acid materials have high thermal potential and good thermal stability, can absorb and release heat during the phase change process, regulate the temperature of the concrete, and improve the thermal management performance of the DEF inhibitor filler.
[0028] Optionally, the nano-aluminum oxide has a particle size of 18 - 32 nm, which is used to improve stability and thermal conductivity.
[0029] Optionally, the silica sol has a mass concentration of 20%. The SiO2 contained in the silica sol has a particle size of 10 - 20 nm and a pH value of about 10. Together with polyvinyl alcohol, it forms a SiO2 / PVA encapsulation layer to prevent the decomposition or leakage of materials in high-temperature environments.
[0030] Optionally, the silane coupling agent includes one or more of KH550, KH560, KH570, and KH792.
[0031] Optionally, the shrinkage reducing agent is one or more of polyether shrinkage reducing agents and polyol shrinkage reducing agents.
[0032] Optionally, during the modification process of the silane coupling agent and the shrinkage reducing agent, since the modification processes of the two are carried out sequentially, the silane coupling agent is located at the bottom layer and directly bonds to the surface of SiO2 / PVA to ensure the interfacial strength; the shrinkage reducing agent is located at the outer layer and is exposed to the surface to regulate water migration.
[0033] A typical embodiment of the present invention provides the preparation method of the above DEF-inhibiting filler, including: S1. Add nano-aluminum oxide to the phase change material in a molten state, stir evenly, and then mix it with calcined straw particles, so that the phase change material is adsorbed into the voids of the calcined straw particles. Cool down to below the phase change temperature of the phase change material to obtain the filler adsorbed with the phase change material; S2. Dissolve silica sol and polyvinyl alcohol in deionized water together to obtain an encapsulating solution. Immerse the filler adsorbed with the phase change material in the encapsulating solution, take it out, and modify it with a silane coupling agent and a shrinkage reducing agent in sequence to obtain the DEF-inhibiting filler.
[0034] Optionally, the preparation method of the calcined straw particles includes: Select dry straw (water content ≤ 5%), crush it to a particle size ≤ 5 mm, and remove impurities; Calcinate the crushed straw at 500 ± 10 °C for 2 - 4 hours, naturally cool it, and then screen to obtain 1 - 3 mm particles. Immerse them in a NaOH solution, stir magnetically (300 - 400 rpm) for 30 - 40 min, wash with deionized water until neutral, and dry at 80 - 100 °C for 12 - 14 h.
[0035] Optionally, in S1, the adsorption method is vacuum impregnation, the vacuum degree is less than 10 -4 Pa, the impregnation time is 3 - 5 h to ensure that the PCM completely fills the pores of the aggregate. After restoring the normal pressure, let it stand for 3 - 5 h to make the PCM evenly fill the pores of the aggregate. Take out the filler adsorbed with PCM, and cool it to room temperature at a set rate.
[0036] Optionally, in S2, dissolve silica sol and polyvinyl alcohol in deionized water together and stir until it becomes a transparent colloid to obtain an encapsulating solution. In the encapsulating solution, the mass concentration of silica sol is 5 - 10%, and the mass concentration of polyvinyl alcohol is 0.5 - 1.0%.
[0037] Optionally, in S2, after immersing the filler adsorbed with the phase change material in the encapsulating solution for 60 - 90 s, take it out and drain it, dry it at a temperature below the phase change temperature for 2 - 4 h, spray a silane coupling agent to seal the surface micropores, and dry it at 60 - 80 °C for 2 - 4 h. Then spray a shrinkage reducing agent SRA to evenly cover the surface of the aggregate and dry it naturally for 12 - 14 h; Ensure the stable adsorption of SRA and improve the crack resistance of the aggregate.
[0038] A typical embodiment of the present invention provides a crack-resistant UHPC, including the following components in parts by weight: 360 - 520 parts of high sulfate resistant cement, 36 - 52 parts of silica fume, 36 - 52 parts of calcined straw ash, 7 - 36 parts of nano-silica modified plant fiber, 800 - 1000 parts of fine aggregate, 800 - 1000 parts of coarse aggregate, 39 - 78 parts of steel fiber, 10 - 15 parts of low-temperature calcined nano-magnesium oxide, 8 - 12 parts of high-temperature calcined micro-magnesium oxide, 80 - 200 parts of the above DEF inhibitor filler, 5 - 18 parts of nano-silica aerogel, 120 - 130 parts of water, 2 - 6 parts of shrinkage reducing agent and 5 - 10 parts of water reducing agent.
[0039] Among the above components, the calcined straw ash, as a partial substitute material for cement, can reduce the release of hydration heat, lower the internal temperature rise of concrete, and prevent cracks caused by thermal stress; the hydration product Mg(OH)2 of magnesium oxide does not decompose at high temperatures, and the synergistic effect of micro-scale and nano-scale magnesium oxide can achieve full-process expansion compensation through the differences in particle size and calcination temperature; the low thermal conductivity of nano-silica aerogel can significantly reduce the overall thermal conductivity of concrete, enabling it to reduce the heat transfer from the surrounding rock in a deep-buried high geothermal environment and avoid temperature stress concentration; nano-SiO2 modified plant fibers with different lengths build a reinforcing network for bridging cracks inside the concrete, and have the ability to absorb / release water, optimizing the internal curing effect, thereby improving the service stability of UHPC and enabling it to adapt to long-term engineering applications in extreme environments.
[0040] Optionally, the high sulfate resistant cement is selected from 52.5 grade or 52.5R grade high sulfate resistant cement; the content of tricalcium aluminate is relatively low (C3A ≤ 5%), which means that the content of calcium aluminate in the cement that can react with sulfate ions to form ettringite (AFt) is less; therefore, the use of high sulfate resistant cement significantly reduces the occurrence probability of DEF, effectively avoiding the crack problem caused by ettringite expansion; it can reduce the potential negative impact of sulfate on concrete, enhance the crack resistance and high-temperature resistance of concrete; and has good compatibility with polycarboxylate superplasticizer.
[0041] Optionally, the calcined straw ash includes low-temperature calcined straw ash and medium-temperature calcined straw ash with a mass ratio of 1:(0.8 - 1.2); the low-temperature calcined straw ash is calcined at a temperature below 500°C, mainly amorphous SiO2, and its porous structure can adsorb ions in the early stage of hydration; the medium-temperature calcined straw ash is calcined at 500 - 600°C, containing high-activity SiO2 / Al2O3, and continuously generates C-S-H gel in the middle and late stages of the hydration reaction. The compounding of the two kinds of calcined straw ash synergistically realizes the characteristics of low heat + high strength, and is suitable for temperature control projects in high geothermal and high ground stress environments.
[0042] Optionally, in the nano-silica modified plant fiber, the plant fiber is selected from one or more of hulless barley straw fiber, wheat straw fiber, flax fiber and bamboo fiber, and includes short fibers of 3 - 6 mm and long fibers of 6 - 12 mm. The volume ratio of the short fibers to the long fibers is 1 - 1.5. The short fibers are used to fill the micro-pores of the concrete to inhibit early plastic shrinkage; the long fibers are used to span micro-cracks, and improve the crack resistance by fiber pull-out energy dissipation.
[0043] Optionally, the fine aggregate is river sand or quartz sand, with a fineness modulus of 2.3 - 3.0, a particle size of 0.075 - 0.35 mm, and an average particle size of 0.2 mm.
[0044] Optionally, the Mohs hardness of the coarse aggregate is not less than 8, the elastic modulus is 400 - 450 GPa, and the density is 3300 kg / m 3 。
[0045] Optionally, the particle size of the micron-sized magnesium oxide after high-temperature calcination is 5 - 10 µm, the calcination temperature is 800 - 1000 °C, and the specific surface area is 0.16 - 0.34 m 2 / g; the particle size of the nano-sized magnesium oxide after low-temperature calcination is 100 - 500 nm, the calcination temperature is 500 - 600 °C, and the specific surface area is 3.36 - 16.8 m 2 / kg.
[0046] The micron-sized magnesium oxide after high-temperature calcination undergoes grinding and calcination processes in sequence. High-temperature calcination can promote the growth of magnesium oxide crystals, lattice reconstruction, reduce lattice defects, form a dense crystal structure, thereby reducing the surface energy, enhancing the thermodynamic stability, and causing the desorption of surface hydroxyl groups (-OH) at high temperature; delaying its dissolution rate in an alkaline environment; forming a slow-release MgO component.
[0047] The nano-sized magnesium oxide after low-temperature calcination undergoes grinding and calcination processes in sequence. Compared with the high-temperature calcination process, its crystal growth is restricted, the particle size is small, and high defects are retained; low-temperature dehydration can also retain a large number of surface hydroxyl groups and lattice distortion, and the high specific surface area provides abundant reaction sites, accelerating the early Mg 2+ release; it can quickly react with cement hydration products (such as Ca(OH)2) to generate expansive Mg(OH)2, and offset the plastic shrinkage stress in time.
[0048] The hydration reaction of nano-sized magnesium oxide occurs in the early stage of concrete curing, and the hydration reaction of micron-sized magnesium oxide occurs in the middle and late stages of concrete curing; by further adjusting the calcination temperature to increase the hydration rate of nano-sized magnesium oxide and further slow down the hydration rate of micron-sized magnesium oxide, the time period for the shrinkage compensation effect of the magnesium oxide expansive agent can be further extended, realizing the full-process shrinkage compensation in a high geothermal environment.
[0049] Optionally, the average particle size of the nano-silica aerogel is 20-40 nm, the porosity is ≥94%, and the thermal conductivity is 0.016-0.018 W / (m•K).
[0050] A typical embodiment of the present invention provides the above-mentioned preparation method of crack-resistant UHPC, including the steps: S3. Mix dry high sulfate-resistant cement, silica fume, fine aggregate, coarse aggregate, nano-sized magnesium oxide calcined at low temperature, micron-sized magnesium oxide calcined at high temperature, shrinkage reducing agent, fine aggregate, DEF inhibitor filler and shrinkage reducing agent to obtain a dry mixture. S4. Add 60-70% of the total water amount to the dry mixture, stir, then add a high-range water reducer, stir, add the remaining water and calcined straw ash, stir, and then add nano-silica aerogel, stir, and then add nano-silica modified plant fiber and steel fiber to obtain a mixed slurry. S5. Cast the mixed slurry into a mold and cure it at a temperature consistent with the high geothermal environment to obtain crack-resistant UHPC.
[0051] Optionally, the preparation method of the nano-silica modified plant fiber includes: cutting the plant fiber after natural drying to a set length, immersing the fiber in an ethanol-ammonia-tetraethoxysilane (TEOS) mixed sol, ultrasonic dispersing for 20-30 min, standing and reacting for 24-36 h, hydrolyzing and condensing tetraethoxysilane (TEOS) to form amorphous nano-SiO2, uniformly depositing on the fiber surface, and then drying to obtain nano-silica modified plant fiber.
[0052] Optionally, in S3, stir at a low speed for 2-3 min.
[0053] Optionally, in S4, continue to stir for 3-5 min after adding all the water and nano-silica aerogel.
[0054] Optionally, in S4, stir at a medium speed for 3-5 min after adding steel fiber; Optionally, in S5, stir at a high speed for 1-2 min before pouring.
[0055] Optionally, in S5, when casting, a vibrating table can be used to vibrate slightly for 1-2 min, which helps to discharge air bubbles and improve its density.
[0056] Optionally, in S5, after casting, cover it with a plastic film to prevent surface water loss and demold after 24 h.
[0057] Optionally, in S5, cover the surface of the concrete after demolding with a self-adhesive curing film, and avoid generating air bubbles and wrinkles during the laying process; continue to cure the concrete covered with the self-adhesive curing film at a set temperature condition until a set time.
[0058] A typical embodiment of the present invention provides the application of the above crack-resistant UHPC, including: applications in geothermal engineering, deep-buried tunnels, nuclear power plants or infrastructure construction in high geothermal environments.
[0059] Example 1 A DEF inhibitor filler, the preparation raw materials include the following components in parts by weight: 80 parts of calcined straw particles, 20 parts of phase change material, 2 parts of nano-aluminum oxide, 2 parts of silica sol (SiO2), 0.2 part of polyvinyl alcohol (PVA), 25 parts of deionized water, 5 parts of shrinkage reducing agent (SRA), and 0.5 part of silane coupling agent.
[0060] The calcined straw particles are derived from agricultural waste of highland barley.
[0061] The phase change material is composed of palmitic acid and stearic acid mixed in a mass ratio of 6:4.
[0062] The nano-aluminum oxide has a particle size of 18 - 32 nm.
[0063] The silica sol has a mass concentration of 20%, the particle size of the silicon dioxide therein is 10 - 20 nm, and the pH value is 10.
[0064] The polyvinyl alcohol is added in the form of a 10% mass concentration polyvinyl alcohol solution.
[0065] The preparation method includes: S1. Select a set number of palmitic acid and stearic acid and mix them. Heat to 70°C and melt, then add nano-aluminum oxide and continue stirring for 30 min to improve stability and thermal conductivity, and obtain composite PCM at room temperature; select dry highland barley straw (water content ≤ 5%), crush it to a particle size ≤ 5 mm, and remove impurities; put the crushed straw into a muffle furnace, calcine at 500 ± 10°C for 2 h, cool naturally, sieve to obtain 1 - 3 mm particles, soak them in NaOH solution and stir magnetically (300 rpm) for 30 min, wash with deionized water until neutral, and then dry at 80°C for 12 h to obtain calcined straw particles; put the calcined straw particles (1 - 3 mm) into a vacuum tank, evacuate to 10⁻ 4 Pa; inject the molten composite PCM at 60°C, maintain vacuum impregnation for 3 h, then gradually restore normal pressure and continue to stand for 3 h to ensure that the PCM is completely filled in the pores of the aggregate, take out the aggregate adsorbed with the phase change material, cool from 70°C at a rate of 2°C / min to obtain the filler adsorbed with the phase change material.
[0066] S2. Dissolve colloidal silica and polyvinyl alcohol in deionized water and stir until a packaging liquid in the form of a transparent colloid is obtained. Immerse the filler adsorbed with the phase change material in the packaging liquid for 60 s, take it out, drain the excess liquid, and spread it flat on a tray (it can be known by weighing the remaining packaging liquid that in this example, 2 parts of colloidal silica (SiO2), 0.2 part of polyvinyl alcohol (PVA), and 25 parts of deionized water are consumed). Dry it at 60 °C for 2 h, and then spray the hydrolyzed solution of silane coupling agent KH-550 (mix silane coupling agent KH-550 with deionized water and absolute ethanol at a volume ratio of 1:5:20, and stir magnetically for 10 minutes to form a hydrolyzed solution) evenly on the surface of the packaged aggregate in the form of a spray. Spread the sprayed aggregate on a tray, place it in an oven at 60 °C and let it stand for 30 min, and naturally cool to room temperature to seal the surface micropores. Then spray a polyalcohol shrinkage reducing agent (SRA) on the surface to evenly cover the surface of the aggregate, and naturally dry it at 20 ± 5 °C for 12 h to ensure the stable adsorption of SRA and improve the crack resistance of the aggregate, thereby obtaining a DEF inhibitor filler.
[0067] Testing its properties includes: the compressive strength is 9.6 Mpa, the phase change temperature is 55 °C, the thermal conductivity is 0.41 W / (m·K), and the PCM leakage rate is 2%.
[0068] Example 2 An anti-cracking UHPC comprises the following components in parts by weight: 480 parts of 52.5R grade high sulfate-resistant cement, 48 parts of incompletely encrypted silica fume, 48 parts of calcined straw ash, 28 parts of nano-silica modified plant fiber, 900 parts of fine aggregate, 135 parts of the DEF inhibitor of Example 1, 1000 parts of coarse aggregate, 12 parts of low-temperature calcined nano-magnesium oxide, 10 parts of high-temperature calcined micro-magnesium oxide, 39 parts of steel fiber, 12 parts of nano-silica aerogel, 4 parts of shrinkage reducing agent, 130 parts of tap water, and 8 parts of polycarboxylate-based superplasticizer.
[0069] The calcined straw ash is selected as calcined highland barley straw ash, which is an agricultural waste along the line. After natural drying, it is ground by a ball mill to a particle size less than 100 μm; then it is divided into two equal volumes, and after being calcined at 500 °C at low temperature and 600 °C at medium temperature respectively, they are mixed to obtain.
[0070] The content of amorphous silica in the incompletely encrypted silica fume is greater than 95 wt%, the specific surface area is greater than 21.0 m 2 / g, and the specific density (ratio to the density of water) is greater than 2.2.
[0071] The fine aggregate is river sand, with a fineness modulus of 2.5 and an average particle size of 0.2 mm.
[0072] The coarse aggregate is selected as basalt, with a Mohs hardness of not less than 8, an elastic modulus greater than 400 GPa, and a density of 3300 kg / m3 。
[0073] The average particle size of nano - magnesium oxide obtained by low - temperature calcination is 400 nm, and the average particle size of micro - magnesium oxide obtained by high - temperature calcination is 6 µm.
[0074] The steel fiber is a copper - plated straight steel fiber with an average length of 13 mm and an average diameter of 0.16 mm. Its tensile strength is greater than 2500 MPa, elastic modulus is 200 GPa, and density is 7800 kg / m 3 。
[0075] The average particle size of nano - silica aerogel is 25 nm, the porosity is ≥94%, the thermal conductivity is 0.018 W / (m•K); the density is 150 kg / m 3 。
[0076] The high - efficiency water - reducing agent is a polycarboxylate - based water - reducing agent, its solid content is greater than 35%, and the density is 1100 kg / m 3 。
[0077] The shrinkage - reducing agent is a polyether - type shrinkage - reducing agent.
[0078] The raw materials of nano - silica - modified plant fibers include highland barley straw and wheat straw, including short fibers of 3 - 6 mm and long fibers of 6 - 12 mm in equal - volume ratio, and the fiber diameter is 10 - 300 µm; it is obtained by immersing the fibers in an ethanol - ammonia - TEOS mixed sol, ultrasonic dispersing for 20 minutes, and standing for reaction for 24 hours, so that tetraethoxysilane (TEOS) hydrolyzes and condenses to form amorphous nano - SiO2 and uniformly deposit on the fiber surface.
[0079] The preparation method includes: S3. Mix high - sulfate - resistant cement, silica fume, fine aggregate, coarse aggregate, nano - magnesium oxide, micro - magnesium oxide, shrinkage - reducing agent, fine aggregate, DEF inhibitor filler and shrinkage - reducing agent and dry - mix at low speed for 3 min to obtain a dry - mixed material.
[0080] S4. Add 70% of the total water volume to the dry - mixed material and stir, add the high - efficiency water - reducing agent, stir and then add the remaining water and calcined straw ash and stir for 5 min. When the fluidity of the fresh concrete is good, slowly add nano - silica aerogel through a square - hole sieve, continue to stir at medium speed for 5 min until uniform, and then slowly add steel fibers and nano - silica - modified plant fibers and stir to obtain a mixed slurry.
[0081] S5. After high-speed stirring the mixed slurry for 2 min, cast it into a mold. During casting, use a vibrating table to gently vibrate for 2 min to discharge air bubbles. After casting, cover it with a plastic film to prevent surface moisture loss, and demold after 24 h. Cover the surface of the demolded concrete with a self-adhesive curing film, and avoid generating air bubbles and wrinkles during the laying process. Keep curing the concrete covered with the self-adhesive curing film at a temperature of 60 ± 2 °C and a humidity of 55 ± 2% until the set time.
[0082] Example 3 An anti-cracking UHPC comprises the following components in parts by weight: 360 parts of high sulfate-resistant cement, 36 parts of silica fume, 36 parts of calcined straw ash, 7 parts of nano-silica modified plant fiber, 800 parts of fine aggregate, 800 parts of coarse aggregate, 39 parts of steel fiber, 10 parts of low-temperature calcined nano-scale magnesium oxide, 8 parts of high-temperature calcined micro-scale magnesium oxide, 80 parts of DEF inhibitor filler in Example 1, 5 parts of nano-silica aerogel, 120 parts of water, 2 parts of shrinkage reducing agent and 5 parts of water reducing agent.
[0083] The specifications and preparation methods of each raw material are the same as those in Example 2.
[0084] Example 4 An anti-cracking UHPC comprises the following components in parts by weight: 520 parts of high sulfate-resistant cement, 52 parts of silica fume, 52 parts of calcined straw ash, 36 parts of nano-silica modified plant fiber, 1000 parts of fine aggregate, 1000 parts of coarse aggregate, 78 parts of steel fiber, 15 parts of low-temperature calcined nano-scale magnesium oxide, 12 parts of high-temperature calcined micro-scale magnesium oxide, 200 parts of DEF inhibitor filler in Example 1, 18 parts of nano-silica aerogel, 130 parts of water, 6 parts of shrinkage reducing agent and 10 parts of water reducing agent.
[0085] The specifications and preparation methods of each raw material are the same as those in Example 2.
[0086] Comparative Example 1 An anti-cracking ultra-high performance concrete, different from Example 2 in that: it does not add calcined straw ash. The specifications and preparation methods of other raw materials are the same as those in Example 2.
[0087] Comparative Example 2 An anti-cracking ultra-high performance concrete, different from Example 2 in that: it does not add nano-SiO2 modified plant fiber. The specifications and preparation methods of other raw materials are the same as those in Example 2.
[0088] Comparative Example 3 An anti-cracking ultra-high performance concrete, different from Example 2 in that: it does not add low-temperature calcined nano-scale magnesium oxide and high-temperature calcined micro-scale magnesium oxide. The specifications and preparation methods of other raw materials are the same as those in Example 2.
[0089] Comparative Example 4 An anti-cracking ultra-high performance concrete, different from Example 2 in that: DEF inhibition filler is not added. The specifications of other raw materials and the preparation method are the same as those in Example 2.
[0090] Comparative Example 5 An anti-cracking ultra-high performance concrete, different from Example 2 in that: nano-silica aerogel is not added. The specifications of other raw materials and the preparation method are the same as those in Example 2.
[0091] Comparative Example 6 An anti-cracking ultra-high performance concrete, different from Example 2 in that: ordinary Portland cement is used to replace the 52.5R grade high sulfate-resistant cement in Example 2; and DEF inhibitor, nano-silica aerogel, low-temperature calcined nano-scale magnesium oxide, high-temperature calcined micro-scale magnesium oxide and calcined straw ash are not added. The specifications of other raw materials and the preparation method are the same as those in Example 2, serving as a blank control.
[0092] Comparative Example 7 A DEF inhibition filler, different from Example 1 in that: shrinkage reducing agent (SRA) is not added. The specifications of other raw materials and the preparation method are the same as those in Example 1.
[0093] Comparative Example 8 An anti-cracking ultra-high performance concrete, different from Example 2 in that: the DEF inhibition filler prepared in Comparative Example 7 is used to replace the DEF inhibition filler prepared in Example 1. The specifications of other raw materials and the preparation method are the same as those in Example 2.
[0094] Comparative Example 9 An anti-cracking ultra-high performance concrete, different from Example 2 in that: all the calcined straw ash is obtained by low-temperature calcination at 500 °C, excluding the calcined straw ash obtained by calcination at 600 °C. The specifications of other raw materials and the preparation method are the same as those in Example 2.
[0095] Comparative Example 10 An anti-cracking ultra-high performance concrete, different from Example 2 in that: the added plant fibers are not modified. The specifications of other raw materials and the preparation method are the same as those in Example 2.
[0096] Performance detection includes: Specimens with a size of 40 * 40 * 40 mm are prepared from each example and comparative example; The slump flow of each example and comparative example is tested during the preparation process; The compressive strength of the specimen is tested when it is cured to the set time after covering with a self-adhesive curing film; Using the flat plate method, the number of cracks on the entire surface of the specimen is detected 24 h under the condition of high geothermal curing, the crack area is calculated through the length and width of the cracks, and the ratio of the crack area of the specimen to the surface area of the specimen is calculated; According to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB∕T 50082-2009), the impermeability grade was evaluated by the water penetration resistance test; The performance test results are shown in Table 1.
[0097] Table 1 Statistical Table of Experimental Data Results
[0098] Example 2 exhibits excellent comprehensive performance compared with each comparative example, especially outstanding in terms of compressive strength, crack resistance and impermeability.
[0099] The experimental data shows that the compressive strength of Example 2 reaches 150.2 MPa, far higher than that of Comparative Example 6 (128.6 MPa), and also shows varying degrees of improvement compared with other comparative examples.
[0100] The number of cracks per unit area in Example 2 is 10.8 cracks / m 2 , far lower than that of Comparative Example 6 (21.6 cracks / m 2 ), and the cracks are reduced by 50%. The total cracking area per unit area is reduced from 2213.5 mm 2 / m 2 of Comparative Example 6 to 454 mm 2 / m 2 , a reduction of 79.5%. Key factors for crack reduction: Calcined hulless barley straw ash, as a pozzolanic active material, partially replaces cement, reducing the heat of hydration. The DEF inhibitor reduces the heat of hydration accumulation and temperature rise through a phase change energy storage material (PCM), inhibits DEF expansion, and improves the long-term volume stability of concrete. Nano-SiO2 modification can enhance the interfacial bonding force between fibers and the cement matrix, provide crack bridging capabilities at different scales, and improve the water absorption / desorption capacity of fibers, optimizing the internal curing effect. The dual-scale magnesium oxide early and long-term shrinkage compensation mechanism effectively reduces autogenous shrinkage and drying shrinkage cracking. Nano-SiO2 aerogel reduces the heat transfer of surrounding rock by reducing the thermal conductivity of concrete, optimizes the temperature gradient, reduces temperature stress cracks, and improves the long-term service performance in high geothermal environments. SRA spraying can reduce the surface tension of capillary water in concrete, reduce autogenous shrinkage stress, and at the same time reduce the incidence of plastic shrinkage cracks through surface moisture retention.
[0101] The reduction of cracks not only improves the overall strength of concrete but also significantly enhances its high-temperature resistance and impermeability. The impermeability grade of Example 2 is higher than that of the comparative example, indicating that the example exhibits more excellent long-term service performance than the comparative example in the deep-buried high-geothermal environment. The optimized temperature gradient control and crack suppression mechanism enable the concrete to maintain structural stability in high-temperature and low-humidity environments, reducing damage caused by temperature stress and humidity gradients, thereby improving its durability in extreme underground engineering environments.
[0102] Combining these innovative points, the present invention provides a crack-resistant ultra-high-performance concrete suitable for deep-buried high-geothermal environments. It is not only superior to existing UHPC in terms of crack resistance, strength, and durability but also improves service stability and reduces the environmental burden by optimizing the temperature gradient and resource utilization of calcined hulless barley straw ash. The present invention can effectively reduce the peak value of hydration heat, inhibit DEF, and reduce temperature stress cracks, ensuring the long-term service performance of concrete in high-geothermal and low-humidity environments. Through the comparison between the examples and the comparative examples, the present invention significantly optimizes the structural stability of UHPC, reduces cracks, and improves impermeability, fully demonstrating the effectiveness and innovation of the proposed method in deep geological engineering.
[0103] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A DEF suppressing filler, characterized in that: It comprises porous calcined straw particles, in which phase change materials are adsorbed; nano-alumina is dispersed in the phase change materials; the outer side of the calcined straw particles is coated with a SiO2 / PVA encapsulation layer, and a silane coupling agent modification layer and a shrinkage reducing agent modification layer are sequentially arranged on the surface of the SiO2 / PVA encapsulation layer.
2. The DEF suppressing filler according to claim 1, characterized in that The preparation material comprises the following parts by weight: 80-100 parts of calcined straw particles, 20-30 parts of phase change material, 2-3 parts of nano-alumina, 2-3 parts of silica sol, 0.2-0.3 parts of polyvinyl alcohol, 0.5-0.7 parts of silane coupling agent and 5-7 parts of shrinkage reducing agent; Or, the calcined straw particles have a particle size of 1-3 mm and a porosity of 60-70%; or, the phase change material includes one or more of palmitic acid, stearic acid, lauric acid, and myristic acid; Or, the silane coupling agent includes one or more of KH550, KH560, KH570 and KH792; Alternatively, the shrinkage reducing agent is one or more of a polyether shrinkage reducing agent and a polyol shrinkage reducing agent.
3. A method for preparing a DEF suppressing filler as claimed in any one of claims 1 to 2, characterized in that: include: S1, adding nano-alumina to the phase change material in a molten state, stirring evenly and mixing with calcined straw particles, so that the phase change material is adsorbed into the gaps of the calcined straw particles, cooling to below the phase change temperature of the phase change material, and obtaining a filler adsorbed with the phase change material; S2. Dissolve silica sol and polyvinyl alcohol in deionized water to obtain encapsulation liquid, immerse the filler adsorbed with phase change material in the encapsulation liquid, take it out, and modify it with silane coupling agent and shrinkage reducing agent in turn to obtain DEF inhibition filler.
4. The method for preparing a DEF suppressing filler according to claim 3, characterized in that: The adsorption method is vacuum impregnation, and the vacuum degree is less than 10 -4 Pa, the immersion time is 3~5h to ensure that PCM completely fills the aggregate pores. After returning to normal pressure, let it stand for 3~5h to allow PCM to evenly fill the aggregate pores. Take out the filler after PCM adsorption and cool it to room temperature at a set rate.
5. The method for preparing the DEF suppressing filler according to claim 3, characterized in that: In S2, the filler adsorbed with phase change material is immersed in the encapsulation liquid for 60 to 90 seconds, taken out and drained, dried for 2 to 4 hours below the phase change temperature, sprayed with silane coupling agent and dried, then sprayed with shrinkage reducing agent and dried for 12 to 14 hours.
6. A crack-resistant UHPC, characterized in that: The invention comprises the following components in parts by weight: 360-520 parts of high sulfate-resistant cement, 36-52 parts of silica fume, 36-52 parts of calcined straw ash, 7-36 parts of nano-silicon dioxide modified plant fiber, 800-1000 parts of fine aggregate, 800-1000 parts of coarse aggregate, 39-78 parts of steel fiber, 10-15 parts of low-temperature calcined nano-grade magnesium oxide, 8-12 parts of high-temperature calcined micron-grade magnesium oxide, 80-200 parts of the DEF inhibition filler as claimed in any one of claims 1-2, 5-18 parts of nano-silicon dioxide aerogel, 120-130 parts of water, 2-6 parts of shrinkage reducer and 5-10 parts of water reducer.
7. The crack-resistant UHPC according to claim 6, characterized in that: The high sulfate-resistant cement is selected from 52.5 grade or 52.5R grade high sulfate-resistant cement; Or, the calcined straw ash includes low-temperature calcined straw ash and medium-temperature calcined straw ash in a mass ratio of 1:(0.8-1.2); Or, in the nano-silicon dioxide modified plant fiber, the plant fiber is selected from one or more of highland barley straw fiber, wheat straw fiber, flax fiber and bamboo fiber; it includes short fibers of 3 to 6 mm and long fibers of 6 to 12 mm, and the volume ratio of the short fibers to the long fibers is 1 to 1.5; Or, the fine aggregate is river sand or quartz sand, with a fineness modulus of 2.3-3.0, a particle size of 0.075-0.35 mm, and an average particle size of 0.2 mm; Or, the Mohs hardness of the coarse aggregate is not less than 8, the elastic modulus is 400-450 GPa, and the density is 3300 kg / m 3 ; Or, the nano-silica aerogel has an average particle size of 20-40 nm, a porosity of ≥94%, and a thermal conductivity of 0.016-0.018 W / (m•K); Alternatively, the particle size of the high-temperature calcined micron-sized magnesium oxide is 5-10 µm, and the calcination temperature is 800-1000°C; the particle size of the low-temperature calcined nano-sized magnesium oxide is 100-500 nm, and the calcination temperature is 500-600°C.
8. A method for preparing crack-resistant UHPC according to any one of claims 6 to 7, characterized in that: Includes steps: S3, dry-mixing high sulfate-resistant cement, silica fume, fine aggregate, coarse aggregate, low-temperature calcined nano-sized magnesium oxide, high-temperature calcined micron-sized magnesium oxide, shrinkage-reducing agent, fine aggregate, DEF-inhibiting filler and shrinkage-reducing agent to obtain a dry mix; S4, add 60-70% of the total water to the dry mix, add a high-efficiency water reducer after stirring, add the remaining water and calcined straw ash after stirring, then add nano-silica aerogel, add nano-silica modified plant fiber and steel fiber after stirring to obtain a mixed slurry; S5. Cast the mixed slurry into a mold and cure it at a temperature consistent with the high ground temperature environment to obtain crack-resistant UHPC.
9. The method for preparing crack-resistant UHPC according to claim 8, characterized in that: The preparation method of nano-silica modified plant fiber includes: cutting the naturally dried plant fiber into a set length, immersing the fiber in an ethanol-ammonia-tetraethoxysilane mixed sol, ultrasonically dispersing for 20 to 30 minutes, standing for reaction for 24 to 36 hours, allowing tetraethoxysilane to hydrolyze and condense to generate amorphous nano-SiO2, which is uniformly deposited on the fiber surface, and then drying to obtain the nano-silica modified plant fiber.
10. An application of the crack-resistant UHPC according to any one of claims 6 to 7, characterized in that: include: Applications in geothermal projects, deep tunnels, nuclear power plants or infrastructure construction in high geothermal environments.
Citation Information
Patent Citations
Preparation method of straw phase change plate with phase change heat storage and insulation function
CN110434974A
Fiber reinforced and toughened composite phase change material as well as preparation and application thereof
CN115477488A
Anti-crack ultra-high performance concrete for water-rich stratum underground engineering as well as preparation method and application of anti-crack ultra-high performance concrete
CN118184273A
Lightweight high-strength concrete as well as preparation method and application thereof
CN118978370A